Management of Chronic Diseases in Sub-Saharan Africa: Cross-Fertilisation between HIV/AIDS and Diabetes Care. (20th November 2012) - van Olmen, Josefien; Schellevis, François; Van Damme, Wim; Kegels, Guy; Rasschaert, Freya
Abstract : There is growing attention for chronic diseases in sub-Saharan Africa (SSA) and for bridges between the management of HIV/AIDS and other (noncommunicable) chronic diseases. This becomes more urgent with increasing numbers of people living with both HIV/AIDS and other chronic conditions. This paper discusses the commonalities between chronic diseases by reviewing models of care, focusing on the two most dominant ones, diabetes mellitus type 2 (DM2) and HIV/AIDS. We argue that in order to cope with care for HIV patients and diabetes patients, health systems in SSA need to adopt new strategies taking into account essential elements of chronic disease care. We developed a "chronic dimension framework, " which analyses the "disease dimension, " the "health provider dimension, " the patient or "person dimension, " and the "environment dimension" of chronic diseases. Applying this framework to HIV/AIDS and DM2 shows that it is useful to think about management of both in tandem, comparing care delivery platforms and self-management strategies. A literature review on care delivery models for diabetes and HIV/AIDS in SSA revealed potential elements for cross-fertilisation: rapid scale-up approaches through the public health approach by simplification and decentralisation; community involvement, peer support, and self-management strategies; and strengthening health services.